Pengaruh Penggunaan Bahan Bakar LGV pada Mobil Penumpang 1200 cc dan 1500 cc Terhadap Kebutuhan Udara dan Bahan Bakar - Amirur Rozak; Nazaruddin Sinaga (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
Manufacture of semiconductor material ofzinc oxide (ZnO) doped with copper (Cu) aims to obtain a good p-type semiconductor material ZnO1-xCuxO. Materials zinc nitrate tetra hydrate and copper nitrate trihydratearean initial material which are combined through a process of mixing the powder in solution with varying content Cu of 0%, 2%, 4%, 6% and 8% mol. Next, the solution is dried, calcined and compacted into pellet form. The pellet is sintered with temperature 1300oC. Results of testing showed the characteristics of materials Zn1-xCuxO containing Cu and testing operating temperature at 450oC generates biggest value for the thermal conductivity of 1.85 W / mK. The amount of material doping affect the the thermal conductivity